2018
DOI: 10.1080/15534510.2018.1439769
|View full text |Cite
|
Sign up to set email alerts
|

Objectified conformity: working self-objectification increases conforming behavior

Abstract: The present work explores whether self-objectification triggered by doing peculiar work activities would increase people's conforming behavior. We conducted an experimental study in which participants (N = 140) were asked to perform a high objectifying activity (vs. low objectifying activity vs. baseline condition) simulating a real computer job. Afterwards, their levels of self-objectification and conforming behavior were assessed. Results revealed that participants who performed the high objectifying activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
1
15
2
Order By: Relevance
“…Overall, the findings of Study 1 followed our hypothesized pattern. However, unexpectedly, and unlike the results of previous studies (Andrighetto et al, 2018), only the self-objectification dimension of instrumentality seems to be involved in this process. Instead, the dimension of (reduced) self-attribution of mental states was not associated with workers' conformity.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Overall, the findings of Study 1 followed our hypothesized pattern. However, unexpectedly, and unlike the results of previous studies (Andrighetto et al, 2018), only the self-objectification dimension of instrumentality seems to be involved in this process. Instead, the dimension of (reduced) self-attribution of mental states was not associated with workers' conformity.…”
Section: Resultscontrasting
confidence: 99%
“…Therefore, both studies confirmed the key role of self-objectification in predicting greater conformity among workers as a consequence of perceiving a task as objectifying (Study 1) or of recalling an objectifying activity (Study 2). However, unexpectedly and unlike previous evidence (Andrighetto et al, 2018), in both studies, only the instrumental dimension of self-objectification played a significant role, whereas the self-attribution of human mental states was not significantly associated with conformity.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations